Protocol for a systematic review and meta-analysis of the placebo response in treatment-resistant depression: comparison of multiple treatment modalities. Issue 2 (16th February 2021) - Jones, Brett D M; Weissman, Cory R; Razza, Lais B; Husain, M Ishrat; Brunoni, Andre R; Daskalakis, Zafiris J
Abstract : Introduction: The high placebo response in depression treatment trials is a major contributing factor for randomised control trial failure to establish efficacy of novel or repurposed treatments in treatment-resistant depression (TRD) and major depressive disorder in general. Though there have been a number of meta-analyses and primary research studies evaluating the placebo response in non-TRD, placebo response in TRD is poorly understood. It is important to understand the placebo response of TRD as treatments are only moderately effective and up to 1/3 of patients will experience TRD. Methods and analysis: We will conduct a search of electronic databases (MEDLINE and PsychINFO) from inception to 24th January 2020 including randomised, placebo-controlled trials of pharmacological, somatic and psychological interventions for adults with TRD. TRD will be defined as a failure to respond to at least two interventions of adequate dose or duration. We will also search reference lists from review articles. We will perform several meta-analyses to quantify the placebo response for each treatment modality. Regression analysis will explore potential contributing demographic and clinical variables to the placebo response. We will use Cochrane risk of bias tool. Ethics and dissemination: There is no research ethics board approval required. The dissemination plan is to publish results in a peer-reviewed academic journal. PROSPERO registration number: 190 465.